Iris melanoma outcomes based on the Cancer Genome Atlas (TCGA) classification in 78 consecutive patients. (2nd November 2022) - Cherkas, Elliot; Negretti, Guy S.; Zeiger, Jennifer S.; Shields, Carol L.
ABSTRACT: Background: The Cancer Genome Atlas (TCGA) classification of genetic alterations in uveal melanoma is widely used for prognostication. We present novel observations on the impact of TCGA Group specifically for iris melanoma. Methods: This was a retrospective cohort study at a tertiary referral ocular oncology center. All patients with a diagnosis of iris melanoma who underwent genetic evaluation and assessment for TCGA classification between 20 November 1995 and 5 April 2021 were included. The main outcome measures were visual acuity, secondary glaucoma, tumor recurrence, melanoma-related metastasis and death per TCGA group. Results: There were a total of 78 patients included. The mean patient age was 49.6 years (median 53.0, range 3.0–85.0), mean tumor basal diameter was 6.7 mm (median 6.0, range 1.5–22.0), and mean tumor thickness was 2.6 mm (median 2.5, range 0.5–8.5). Cytology results confirmed iris melanoma (93%) or were inconclusive (7%). The TCGA groups included Group A (n = 36, 46%), Group B (n = 7, 9%), Group C (n = 34, 44%), and Group D (n = 1, 1%). There was no statistically significant difference in outcomes of visual acuity, tumor thickness reduction, secondary glaucoma, tumor recurrence, melanoma-related metastasis or death per individual TCGA group (A vs. B vs. C vs. D) and per bimodal comparison (A/B vs. C/D). Conclusions: In this analysis, iris melanoma was classified as TCGA group A or B in 55% and as C or D in 45%. The TCGA classification was not predictive of melanoma-related metastasis or death.